The Potential of Community-Based Nomadic Tourism Development: Insight from Three Case Study in Yogyakarta - Lindawati, Lisa; Damayanti, Acniah; Putri, Dinda Hermiranti (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2021)
Since February 2015, the government has provided tourism as a leading sector in development. It is, however, that this premise needs to be reviewed. As one of the popular destinations in Indonesia, after Bali, Yogyakarta is still dealing with acute poverty problems with an 11,7% poverty rate and disparity index of 0,423 (Gini ratio) by March 2019. This situation showed that tourism has not contributed to its vital role in empowering the community. The primary problem is concerning the lack of participation based-community in developing and managing tourism. Regarding that problem, community-based tourism is present as an alternative tourism model because it is concerned with optimizing local potentiality and local community empowerment. Meanwhile, some aspects, including access, amenities, and attractions, are essential in tourism development. In line with issues, the acceleration of digital technology has encouraged nomad workers and experience-based tourism attraction—both elements then actualized in nomadic tourism. According to the case study method, this research has investigated the potentiality of the nomadic tourism model in the Special Region of Yogyakarta: Bukit Kosakora (Kosakara Hill) in Gunung Kidul, Taman Bambu Air (Water Bamboo Park) in Sermo Reservoir, Kulonprogo, and Bukit Lintang Sewu (Thousand Stars Hill) in the Mangunan, Bantul, Yogyakarta. The three places are potentially pioneers of nomadic tourism in Yogyakarta. The research results highlight that all of these places have amenities, attraction, and access as opportunities to be nomadic tourism. However, they have implemented the basic principles of community-based tourism, but the realization is not yet fully optimal because of the matter in the institutional context.